Vulvodynia: Assessment and Treatment. Issue 4 (1st April 2016) - Goldstein, Andrew T.; Pukall, Caroline F.; Brown, Candace; Bergeron, Sophie; Stein, Amy; Kellogg-Spadt, Susan
ABSTRACT: Introduction: Vulvodynia constitutes a highly prevalent form of sexual pain in women, and current information regarding its assessment and treatment is needed. Aim: To update the scientific evidence published in 2010, from the Third International Consultation on Sexual Medicine, pertaining to the assessment and treatment of women's sexual pain. Methods: An expert committee, as part of the Fourth International Consultation on Sexual Medicine, was comprised of researchers and clinicians from biological and social science disciplines for the review of the scientific evidence on the assessment and treatment of women's genital pain. Main Outcome Measures: A review of assessment and treatment strategies involved in vulvodynia. Results: We recommend the following treatments for the management of vulvodynia: psychological interventions, pelvic floor physical therapy, and vestibulectomy (for provoked vestibulodynia). We also support the use of multidisciplinary treatment approaches for the management of vulvodynia; however, more studies are needed to determine which components are most important. We recommend waiting for more empirical evidence before recommending alternative treatment options, anti-inflammatory agents, hormonal agents, and anticonvulsant medications. Although we do not recommend lidocaine, topical corticosteroids, or antidepressant medication for the management of vulvodynia, we suggest that capsaicin, botulinum toxin, and interferon be considered second-line avenues and that their recommendation be revisited once further research is conducted. Conclusion: A comprehensive assessment is needed to understand the pain experience of women presenting with vulvodynia. In addition, treatment typically progresses from less invasive to more invasive, and several treatment options are worth pursuing.